The synergy between life’s essential 8 and muscle strength on cardiovascular disease risk - Li, Linlong; Xu, Jianhong; Huang, Li; Tu, Xiangping; Lin, Taiping; Yue, Jirong; Ge, Ning; Wu, Chenkai (Frontiers in Medicine, 2025)
BackgroundWhile muscle strength is a known CVD risk factor in aging, its influence across the spectrum of Life’s Essential 8 (LE8) scores - the American Heart Association’s (AHA’s) comprehensive metric of cardiovascular health that includes diet, physical activity, sleep, nicotine exposure, body mass index, blood lipids, blood glucose, and blood pressure - remains unclear.MethodsWe analyzed data from 237,682 individuals (mean age 55.64 ± 8.06 years) from UK Biobank. Muscle strength was assessed by grip strength and categorized into high, medium, and low based on tertiles. LE8 was classified into ideal (≥80), medium (50–79), and low (<50) based on AHA guideline. We used the Cox regression to examine the joint association of muscle strength and LE8 with incident CVD, including coronary heart disease, heart failure (HF) and stroke. Both multiplicative and additive interactions were examined.ResultsOver a median 14.90-year follow-up, 26,159 incident CVD cases were recorded. Reduced muscle strength was not associated with CVD risk among persons with ideal LE8 (medium vs. high: HR = 0.91, 95% CI 0.79–1.05; low vs. high: HR = 1.03, 95% CI 0.90–1.17). However, a significant additive interaction was observed between low muscle strength and a low LE8 score, which accounted for 17% (AP = 0.17, 95% CI 0.10–0.24) of the excess CVD risk and corresponded to a threefold increased risk (HR = 3.03, 95% CI 2.72–3.37). This synergistic effect was particularly pronounced for HF, women, and younger individuals (<56 years). Among the individual LE8 components, blood glucose exhibited the strongest additive interaction with low muscle strength (RERI = 0.31, 95% CI 0.13–0.49; AP = 15, 95% CI 7–23%), followed by sleep, nicotine exposure, BMI, and physical activity.ConclusionThe cardiovascular risk associated with low muscle strength is contingent upon overall cardiovascular health. It poses a significant threat specifically when co-existing with poor cardiovascular health (a low LE8 score), highlighting the need for targeted interventions in this high-risk subgroup.